1998
DOI: 10.1130/0016-7606(1998)110<0985:lceotc>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Late Cenozoic exhumation of the Cascadia accretionary wedge in the Olympic Mountains, northwest Washington State

Abstract: The apatite fission-track method is used to determine the exhumation history of the Olympic subduction complex, an uplifted part of the modern Cascadia accretionary wedge. Fission-track ages are reported for 35 sandstones from the Olympic subduction complex, and 7 sandstones and 1 diabase from the Coast Range terrane, which structurally overlies the Olympic subduction complex. Most sandstone samples give discordant results, which means that the variance in grains ages is much greater than would be expected for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
742
2
8

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 727 publications
(783 citation statements)
references
References 91 publications
(111 reference statements)
31
742
2
8
Order By: Relevance
“…They found that apatite ages were reset over a much broader area (outer bold line in Figure 20) consistent with exhumation of the entire core but to a lesser degree. Cooling rates derived from these apatite data were the same as those based on the zircon ages, suggesting that exhumation rates have remained constant over at least the last 12 Ma [Brandon et al, 1998]. This supports the premise that the exhumation rates are in steady state, and insofar as erosion rates depend on the topography, the topography must also be in steady state.…”
Section: Natural Systemssupporting
confidence: 67%
“…They found that apatite ages were reset over a much broader area (outer bold line in Figure 20) consistent with exhumation of the entire core but to a lesser degree. Cooling rates derived from these apatite data were the same as those based on the zircon ages, suggesting that exhumation rates have remained constant over at least the last 12 Ma [Brandon et al, 1998]. This supports the premise that the exhumation rates are in steady state, and insofar as erosion rates depend on the topography, the topography must also be in steady state.…”
Section: Natural Systemssupporting
confidence: 67%
“…A simple explanation is an earlier P-C phase, followed by the transition to P-U-(C?). This combination accounts for the tectonic underplate, the uplift and denudational exhumation of the core of the Olympic Mountains, and the rotation of the Coast Range Terrane [Tabor and Cady, 1978;Brandon et al, 1998]. The rotation of the backstop clearly indicates a change of mode and demonstrates that the backstop ceased to act in this role when the mode changed.…”
Section: Tectonic Stylesmentioning
confidence: 99%
“…In contrast, the Miocene to recent evolution of the Olympic Mountains segment of the subduction zone has much in common with the P-U mode [Brandon et al, 1998; Willett, submitted manuscript, 1999]. This segment of the subducting plate has an uncharacteristically shallow dip of 11 o or less beneath the accretionary wedge.…”
Section: Tectonic Stylesmentioning
confidence: 99%
See 1 more Smart Citation
“…4.3.3). This pattern of exhumation has been found by the study of the sand-size glacial outwash material using zircon fission-track dating (Enkelmann et al, , 2010, which records the time of cooling below 250 ± 40°C (Brandon et al, 1998). Exhumation of 8-10 km since 2-3 Ma have been estimated for the eastern syntaxis region and explained through the development of a positive feedback between localized strain concentration and efficient glacial erosion .…”
Section: Mountain Building and Erosionmentioning
confidence: 99%